Соціально-економічне регулювання територій в умовах цифрової трансформації - Іванченко, Альона Олександрівна; Ivanchenko, Alyona Oleksandrivna (Ірпінь, 2024)
Формування теоретичних підходів до соціально – економічного регулювання територіальним розвитком під впливом цифровізації та удосконалення підходів до розвитку економіки регіону в умовах діджиталізації, що дозволяє оптимізувати процеси розробки стратегій соціальноекономічного розвитку регіонів. Розкрито сутність соціально-економічного регулювання територіальним розвитком під впливом цифровізації, проведено аналіз економічного і соціального розвитку Київської області, здійснено аналіз процесів цифрової трансформації регіонів України.

The formation of theoretical approaches to socio-economic regulation of territorial development under the influence of digitalization and improvement of approaches to the development of the regional economy in conditions of digitalization, which allows optimizing the processes of developing strategies for the socio-economic development of regions. The essence of socio-economic regulation of territorial development under the influence of digitalization was revealed, an analysis of the economic and social development of the Kyiv region was carried out, and an analysis of the processes of digital transformation of the regions of Ukraine was carried out.
Socio-economic regulation of territories in the conditions of digital transformation
Keywords: соціально-економічне регулювання територій; цифрові трансформації; Київська область; socio-economic regulation of territories; digital transformations; Kyiv region